Factors Associated with Miscarriages and Abortions among Women of Reproductive Age in Kyrgyzstan: An Analysis of the Multiple Indicators Cluster Survey 2023 - Indrawati, Fitri; Supriatin, Supriatin; Maretalinia, Maretalinia; Yunus, Mohd (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Reproductive health, including miscarriages and abortions, remains a critical public health issue, especially in low- and middle-income countries such as Kyrgyzstan, where access to quality health services is limited, particularly in rural areas. Unsafe abortions contribute significantly to maternal morbidity and mortality, while miscarriages can have physical, emotional, and social consequences for women. This study aims to explore factors associated with miscarriages and abortions among women of reproductive age in Kyrgyzstan. This study used secondary data from Kyrgyzstan’s Multiple Indicator Survey (MICS) 2023, which provides comprehensive data on health, education, and living conditions. The survey focused on women aged 15–49 who had experienced miscarriage or abortion, analyzing factors such as age, marital status, education, and wealth index. Data analysis was performed using binary logistic regression with STATA software to identify demographic and socioeconomic factors associated with miscarriage and abortion. The finding of this study were 11.47% of women experienced miscarriage and 6.45% experienced abortion, with most participants aged 30-39, married, with a junior high school education, residing in rural areas, and belonging to the Kyrgyz ethnic group. Factors linked to miscarriage included age, marital status, rural residency, Russian ethnicity, and wealth level, while factors associated with abortion included age, marital status, rural residence, and certain wealth levels (second, middle, and fourth). The study suggests prioritizing reproductive health education and support for women, especially those in rural areas and with lower to middle income, to help reduce the risks of miscarriage and abortion.